Management of apicomarginal defect in esthetic region associated with a tooth with anomalies - Vinayak Venkoosa Meharwade; Dipali Yogesh Shah; Pradyna Prabhakar Mali; Vinayak Meharwade (Korean Academy of Conservative Dentistry, 2015)
Tooth related factors such as palatoradicular groove can be one of the causes for localized periodontal destruction. Such pathological process may result in apicomarginal defect along with inflammation of pulp. This creates challenging situation which clinician must be capable of performing advanced periodontal regenerative procedures for the successful management. This case report discusses clinical management of apicomarginal defect associated with extensive periradicular destruction in a maxillary lateral incisor, along with histopathologic aspect of the lesion.